Analysis of public service cauldron on customer satisfaction at bank Republik Indonesia Kefamenanu branch - Berno Benigno Mitang; Emilia Khristina Kiha (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The quality of service provides encouragement to customers, to establish a strong bond with the company. Such a bond in the long term allows the company to carefully understand the expectations of customers and their needs so that the company can increase customer satisfaction where the company maximizes a pleasant customer experience and minimizes the customer experience that is less pleasant. The purpose of this research is to find out how to analyze the quality of service to determine customer satisfaction at the PT. Bank Republik Indonesia Kefamenanu Branch, and in this study we used Multiple Regression Analysis. The test results revealed that the quality of service had a limited impact on customer satisfaction. The coefficient of determination (R2) shows that the quality of service contributes 0.643, or 64.3%, to customer satisfaction, with the remaining 52.8% coming from other factors not studied in this study.